Effects of van der Waals density functional corrections on trends in furfural adsorption and hydrogenation on close-packed transition metal surfaces. - Liu, Bin; Cheng, Lei; Curtiss, Larry; Greeley, Jeffrey (My University, 2014)
The hydrogenation of furfural to furfuryl alcohol on Pd(111), Cu(111) and Pt(111) is studied with both standard Density Functional Theory (DFT)-GGA functionals and with van der Waals-corrected density functionals. VdWDF functionals, including optPBE, optB88, optB86b, and Grimme's method, are used to optimize the adsorption configurations of furfural, furfuryl alcohol, and related intermediates resulting from hydrogenation of furfural, and the results are compared to corresponding values determined with GGA functionals, including PW91 and PBE. On Pd(111) and Pt(111), the adsorption geometries of the intermediates are not noticeably different between the two classes of functionals, while on Cu(111),modest changes are seen in both the perpendicular distance and the orientation of the aromatic ringwith respect to the planar surface. In general, the binding energies increase substantially inmagnitude as a result of van derWaals contributions on all metals. In contrast, however, dispersion effects on the kinetics of hydrogenation are relatively small. It is found that activation barriers are not significantly affected by the inclusion of dispersion effects, and a Brønsted–Evans–Polanyi relationship developed solely fromPW91 calculations on Pd(111) is capable of describing corresponding results on Cu(111) and Pt(111), even when the dispersion effects are included. Finally, the reaction energies and barriers derived from the dispersion-corrected and pure GGA calculations are used to plot simple potential energy profiles for furfural hydrogenation to furfuryl alcohol on the three considered metals, and an approximately constant downshift of the energetics due to the dispersion corrections is observed.
Keywords: Furfural hydrogenation; Periodic Density Functional Theory; Van der Waals density functional; Linear scaling relationship; Brønsted–Evans–Polanyi relationship